Quantifying Salmonella contamination in pig slaughterhouses in Hung Yen, Vietnam - Sinh Dang Xuan; Hung Nguyen-Viet; Tongkorn Meeyam; Fries, R. (Veterinary Public Health Centre for Asia Pacific, 2013)
The risk of Salmonella contamination along the pork production is a worldwide concern. Not only the biological contamination, but also personal perception and individual behavior play a role for risk assessment along a chain. This study is to identify the prevalence and number of Salmonella in 3 pig slaughterhouses in relation to several risk factors. During January to April 2013, a total of 87 samples (carcasses, workers’ hands, cutting board and belly skin material) were collected from 4 visits to each slaughterhouse. A 3-tube Most Probable Number (MPN) was applied to quantify the number of Salmonella from carcass, workers’ hands, cutting board and belly skin samples (35 samples). The result showed that Salmonella prevalence was 36.9% (26.7-47.8%), mostly found on worker’s hands (50%) and the lowest from cutting board (33.3%). The highest number of Salmonella on carcass and cutting boards was less than 0.075 MPN/cm2 and 1.2 MPN/cm2, respectively. Potential risk factors were tested however they were not statistical significant. This study underlines the necessity of good hygiene practices and management in slaughterhouses. In terms of food safety, further risk assessment of Salmonella in pork production chains is needed.